'Yours is the Earth and everything that's in it, and – which is more – you'll be a man, my son': Myths of British masculinity and Britishness in the construction and reception of Iron Maiden. (1st September 2017) - Spracklen, Karl
In the years following the end of the Second World War, the British Empire declined as a global, hegemonic power. In the years of this decline, British children were still taught stirring tales and myths of British military might and British fair-play. In this article, I argue that this mythic milieu served as source of inspiration for Iron Maiden's songs from Iron Maiden (1980) to Somewhere in Time (1986). I show that themes on these albums deliberately reflect and construct this mythic version of Imperial British masculinity. I then explore how the band has continued to play with Britishness globally. I argue that Iron Maiden's members and creators have constructed their creative art around imagined white, British imperial identities. They have been raised in the ways of the mythic milieu, and serve its hegemonic interest, whether they are conscious of that fact or not.